2018
DOI: 10.1038/s41467-017-02573-2
|View full text |Cite|
|
Sign up to set email alerts
|

Maturation of the gut microbiome and risk of asthma in childhood

Abstract: The composition of the human gut microbiome matures within the first years of life. It has been hypothesized that microbial compositions in this period can cause immune dysregulations and potentially cause asthma. Here we show, by associating gut microbial composition from 16S rRNA gene amplicon sequencing during the first year of life with subsequent risk of asthma in 690 participants, that 1-year-old children with an immature microbial composition have an increased risk of asthma at age 5 years. This associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
452
9
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(496 citation statements)
references
References 70 publications
(100 reference statements)
27
452
9
8
Order By: Relevance
“…We found that tracheal colonization in the neonatal period was associated with a decreased risk of asthma. The relationship between lung and gut microbiota and childhood asthma appears to be complex . Nevertheless, our results can be viewed as lending support to the hypothesis that reduced exposure to bacteria in early life may increase the risk of asthma and other atopic diseases …”
Section: Discussionsupporting
confidence: 77%
“…We found that tracheal colonization in the neonatal period was associated with a decreased risk of asthma. The relationship between lung and gut microbiota and childhood asthma appears to be complex . Nevertheless, our results can be viewed as lending support to the hypothesis that reduced exposure to bacteria in early life may increase the risk of asthma and other atopic diseases …”
Section: Discussionsupporting
confidence: 77%
“…The gradual increase of the butyrate levels and the emergence of the butyrogenic community in the gut could be important for gut maturation, as aberrant microbial composition and/or SCFA production is associated with colicky symptoms and atopy diseases in infants (Arrieta et al 2015, de Weerth et al 2013, Stokholm et al 2018, Wopereis et al 2017. …”
Section: Microbial Network Leading To Butyrate Productionmentioning
confidence: 99%
“…An aberrant SCFA profile and/or microbial composition are/is shown to be associated with colicky symptoms and allergy in infants (Arrieta et al 2015, de Weerth et al 2013, Stokholm et al 2018, Wopereis et al 2017. A significant decrease of Lachnospira, Veillonella, Faecalibacterium, and Rothia genera, as well as reduced levels of faecal acetate at 3 months old have been observed in children at risk of asthma (Arrieta et al 2015).…”
Section: Chaptermentioning
confidence: 99%
“…Furthermore, there was a significant difference in the structure of microbial populations at one year in non‐asthmatic children compared with children who had asthma at age five, which was positively associated with higher abundance of Veillonella and lower abundance of Roseburia, Alistipes, Faecalibacterium, Bifidobacterium, Ruminococcus, Lachnospiraceae incertae sedis and Dialister. Interestingly, this association between developing asthma before age 5 and the structure of microbial population was only confined to the children who were born to asthmatic mothers . The association between asthmatic mothers and development of asthma in children has been explained through dysbiosis in a few studies which are discussed in the following section.…”
Section: Dysbiosis In Infancy and Asthma Later In Lifementioning
confidence: 99%